Influence of seed soaking treatment on seed germination and vigour; optimal transplanting seedling age and pruning on agro-morphological performance of Jatropha Curcas L. / Muhamad Syukrie Abu Talip - Abu Talip, Muhamad Syukrie (2016)
Jatropha is a large shrub species which is resistant to drought and low soil fertility thus it has a potential alternative keybiofuel source over declining fossil fuel sources. Due to the several agronomic practices information from other countries it should be tested in environment conditions of Sarawak to achieve optimal yield production. The study explored the nursery techniques and early field establishment with three objectives of Jatropha curcas Linn. The objective of nursery technique was to investigate the germination percentage o f pre-sowing soaking treatment o f seeds on liquid fertilizer. The objectives o f the study on early field establishment were to determine the optimal transplanting age o f Jatropha in the field and to examine the effect of pruning management on the growth parameters and yield o f Jatropha. An experiment using a factorial 3 * 2 Split Plot Design which were consisting of three seedling ages and two pruning management replicated four times was conducted to study early field establishment. The parameters determined were germination percentage, seedling vigour and mortality percentage. The plant performances observed at field planting were plant height, plant collar diameter, branching pattern, flower and fruit production. The treated seeds with liquid fertilizer showed higher germination percentage on Day Four at 72%. However at Day Nine, there were no significant differences with all treatment recorded germination rate o f 97 - 98%. In field condition, one month old seedling showed highest mortality percentage at fifty percent while the two months old seedling showed at 12.5% and four month old seedling was lowest at 6.25%. Generally, there were no significant differences on the plant performance on the seedlings transplanting age as reflected by the number and weight o f nuts recorded at the end o f the period o f study. However, the pruned plants showed significant different in the plants height, primary and secondary branching pattern and bunches production. Furthermore, a strong relationship was shown between the production o f branches and fruit nuts total weight. The study provided evidence that seedling age at two months old was the recommended age for transplanting to the field thus reducing seedling period in the nursery as compared to four months old conventional recommended seedling. Pruning management should be conducted at eight months as there was increased yield. The outcomes o f this study are very significant contribution to Jatropha cultivation in order to have good quality of seedlings and high in production due to good agricultural practice